2012
DOI: 10.1021/ci2004913
|View full text |Cite
|
Sign up to set email alerts
|

Development of Surface-SFED Models for Polar Solvents

Abstract: We developed surface grid-based solvation free energy density (Surface-SFED) models for 36 commonly used polar solvents. The parametrization was performed with a large and diverse set of experimental solvation free energies mainly consisting of combinations of polar solvent and multipolar solute. Therefore, the contribution of hydrogen bonds was dominant in the model. In order to increase the accuracy of the model, an elaborate version of a previous hydrogen bond acidity and basicity prediction model was intro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…The model can provide reliable salvation free energies of experimentally unavailable solute-solvent pairs. Previously, we demonstrated that the solvation free energy density (SFED) model is an efficient one for the description of molecular properties in solution with a linear combination of empirical functions of the solute properties (45)(46)(47)(48)(49)(50). However, the parameterization of the linear expansion coefficients, optimized for each solvent, limits the application of the model to solvents for which the coefficients were determined.…”
Section: Significancementioning
confidence: 99%
See 4 more Smart Citations
“…The model can provide reliable salvation free energies of experimentally unavailable solute-solvent pairs. Previously, we demonstrated that the solvation free energy density (SFED) model is an efficient one for the description of molecular properties in solution with a linear combination of empirical functions of the solute properties (45)(46)(47)(48)(49)(50). However, the parameterization of the linear expansion coefficients, optimized for each solvent, limits the application of the model to solvents for which the coefficients were determined.…”
Section: Significancementioning
confidence: 99%
“…Here we present the generalized SFED (G-SFED) model to calculate the solvation free energies of a molecule including biological molecules in any environment. The effects of the solute on various solute-solvent interactions are represented by the basis functions developed earlier (46)(47)(48)(49)(50), and the complementary solvent effects on these interactions are reflected in the coefficients with a few solvent properties.…”
Section: Significancementioning
confidence: 99%
See 3 more Smart Citations